86.2k views
2 votes
Which shows the correct substitution of the values a, b, and c from the equation –2 = –x + x2 – 4 into the quadratic formula? Quadratic formula: x =

User RvanHeest
by
5.2k points

1 Answer

5 votes

Answer:

The answer in the procedure

Explanation:

we have


2=-x+x^(2) -4


x^(2)-x-4-2=0


x^(2)-x-6=0

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


x^(2)-x-6=0

so


a=1\\b=-1\\c=-6

substitute in the formula


x=\frac{-(-1)(+/-)\sqrt{(-1)^(2)-4(1)(-6)}} {2(1)}


x=\frac{1(+/-)√(25)} {2}


x=\frac{1(+/-)5} {2}


x=\frac{1(+)5} {2}=3


x=\frac{1(-)5} {2}=-2

User Mikek
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.